Socio-economic impact and adoption of improved post-rainy sorghum (Sorghum bicolor) production technologies in Maharashtra - CHAPKE, RAJENDRA R; TONAPI, V A (The Indian Journal of Agricultural Sciences, 2018)
Low remuneration and poor adoption of sorghum [Sorghum bicolor (L.) Moench] production technologies were major constraints in drastic decline in area under cultivation. Therefore, evaluation of production potential, adoption, economic and other benefits of the technologies in social perspectives of the farmers was undertaken. The study was conducted with 200 adopted farmers under frontline demonstrations programme organized during five years from 2009-10 to 2013-14 in five districts in two prominent sorghum growing regions in Maharashtra, India. The yield potential and merits were measured by following before and after method, and data were collected through semistructured interview schedule, group meetings, recorded data and empirical observations. The performance of the demonstrated technologies resulted into increase in adoption (27%), higher net returns (170%), followed by grain yield (58%) with better quality (78%) and fodder yield (26%). It enabled to motivate the farmers and increase in area under sorghum by 29% of the adopted farmers. Out of fifteen demonstrated practices, only five practices namely, use of high yielding variety, maintaining plant spacing, use of treated seeds or seed treatment, weed control measures and nitrogen fertilizer application were found suitable by the farmers which can be easily practiced and gave significant results with low cost. Furthermore, the additional returns helped them in spending significantly higher on purchase of household items (111%) followed by, on attending more social functions (109%), purchase of animals (91%), in start of new business (86%), deposit in bank (77%) and investment in farm development activities (62%). It also revealed that more number of family members and years of adoption under FLD programme resulted into high impact. The findings aptly indicated that the impact of the production technologies was very vital in meeting out the farmers’ social, educational, health and financial needs apart from food and fodder. To boost-up the adoption, large family size of the farmers, their dependency on farming and continuing newly selected farmers with field demonstration of location-specific low-cost technologies up to five years should be considered.